In vitro analysis of the mechanical properties of hypoallergenic denture base resins - Hinz, Sebastian; Bensel, Tobias; Bömicke, Wolfgang; Boeckler, Arne Hellmut Wilhelm Fritjof (Materials, 2022)
The development of hypoallergenic denture resins is key to the treatment of patients with allergies to polymethyl methacrylate (PMMA). In this study, the in vitro mechanical properties of hypoallergenic and PMMA denture base resins were compared. Ninety-six test specimens of hypoallergenic denture base resins (Polyan Plus®, Sinomer, TMS Acetal Dental, Erkocryl) and 72 test specimens of PMMA-based denture base resins (Paladon 65, PalaXpress, SR-Ivocap) were fabricated. The flexural strength, elastic modulus, compressive strength, macro- and microhardness, average roughness, water absorption, and water solubility of the resins were measured. None of the hypoallergenic denture resins matched all the mechanical properties of the PMMA resins. Polyan Plus® and TMS Acetal Dental were closest to matching the mechanical properties of the PMMA resins, and TMS Acetal Dental had some superior properties. Consequently, Polyan Plus® and TMS Acetal Dental hypoallergenic resins are recommended for further investigation as potential alternatives to PMMA resins for the fabrication of removable dentures.
Published: 18 May 2022
Gesehen am 01.07.2022